Strengthening 21st-Century Skills: A Community Service Initiative To Improve Computational, Critical, And Creative Thinking In Pre-Service Teachers In Malaysia: Community Service - Wanda Nugroho Yanuarto; Ira Hapsari; Mohamad Ikram Zakaria (International Journal Of Community Service, 2025)
This community service initiative was conducted to strengthen 21st-century skills, particularly computational, critical, and creative thinking, among pre-service teachers at Universiti Teknologi Malaysia (UTM). The program was designed as a training workshop that combined interactive lectures, hands-on activities, and collaborative problem-solving tasks to expose participants to innovative approaches in teaching and learning. A total of sixty pre-service teachers participated in the program, engaging in activities that integrated computational thinking strategies with opportunities for critical reflection and creative expression. Evaluation data were collected through pre- and post-training questionnaires, reflective journals, and group discussions. The findings revealed notable improvements in participants’ ability to analyze problems systematically, apply logical reasoning, and generate innovative solutions within educational contexts. Furthermore, the participants expressed positive attitudes toward adopting these skills in their future teaching practice. This initiative demonstrates the potential of structured community service programs to support the development of essential 21st-century competencies among pre-service teachers, contributing to the broader goal of preparing future educators to meet the challenges of contemporary education.